Aplikasi Rute Picking Order pada Gudang Menggunakan Metode Algoritma Harmony Search Berbasis Android - Karina Shelvi Gunawan; Andreas Handojo; Tanti Octavia (Jurnal Infra, 2020)
Warehouse is an important element in logistic. Warehouse is place to keep raw material, work-in-process material, or finished goods. Warehouse is used to store goods so that it does not easily damaged. Technology is applied to make warehouse system more efficient. It is important for the owner to know what goods are stored in the warehouse or retail store. Incoming, outgoing, and transferred goods must be known to prevent profit loss. To fulfill orders from consumers and to maintain the number of stock items on the shelves in retail store, picking orders are carried out to pick up the items needed from the warehouse. Efficient picking orders can fill orders faster and complete more incoming orders. This application utilizes Harmony Search algorithm to do routing. Routing is made to do picking order at the warehouse to meet demand. The application can also display warehouse map visualizations to make it easier for users. In addition, the use of weight sensors on retail store shelves to detect stock on retail store shelves. Users can fulfill demands based on routes that have been calculated with the Harmony Search algorithm.